Pengaruh keputusan pendanaan, ukuran perusahaan, ukuran dewan komisaris, dan return on asset terhadap nilai perusahaan - Suci Nurahma; Roy Budiharjo (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2022)
The purpose of this research is to investigate the influence of funding decisions, size of the board of commissioners, firm size, and Return on Asset on Firm’s Value. The object of this research is companies LQ45 at the Indonesia Stock Exchange in 2015-2019. The research design used is a quantitative approach with the selection of samples using a purposive sampling method. Total samples in these research were 27 out of 65 companies that met the criteria. The data used are secondary data and data analysis methods used are multiple linear regression tests which include descriptive test, classic assumptions and hypothesis test. The results of the study show Funding Decisions has not significant influence on Firm’s Value, Size of the Board of Commissioners has significant influence on Firm’s value, Firm Size has not significant influence on Firm Value, and Return on Asset has significant influence on Firm’s Value.